Planning Method for Safety Neurosurgical and Computed Tomography Contrast-Data Set Visualization - Аврунін, О. Г.; Хушам, Фарук (MEDWIN, 2019)
Discussed the issues' associated with the development of a computed neurosurgery planning system. An important part is to determine the value of invasive surgical access. The study purpose is to design a methodology for finding the shortest distance between surgical target and peripheral point of the brain tissue with strict adherence considering the type of the brain anatomical structure existing in the path of surgical track (risk map), these two condition used in companion to determine the risk value of the surgical access. The study method consists of two algorithms for calculating the shortest surgical access to the target and assuring the safety by avoiding high-density tissues identification method “internal map” describing the anatomy of the brain such as bones. An algorithm for automatic identification of brain vascular system also was designed. The structural diagram of the contrast data visualization system, using computed tomography data, was thoroughly discussed. Also, trying to contribute in solving issues facing developers of modern medical imaging visualization systems to select the most appropriate method from the whole arsenal of algorithms and processing models concerning displaying brain surgical zone using image registration and optical tracking system. The visualization of the target zone is carried out according to an internal reference landmark points inside the center of the brain as well as an automatic algorithm for contour recognition was applied. Moreover, the optical tracking system was used to assess the navigation accuracy of determining the position of the surgical instrument outside the patient head. Algorithms necessary for operational planning also was included, and the proposed method was applied in a pilot study with simulation mode to human brain model, in order to target a specific surgical zone, and as a result, the system suggested (24) possible surgical track, among them, were selected the best and safest access. The total error of a surgical instrument targeting was less than 3 mm (in average 2.6 mm).
Keywords: Data visualization; Data processing and displaying; Planning system; Specific surgical access; Risk map